Majorana neutrinos production at LHeC in an effective approach - Duarte, Lucia (2015)
We investigate the possibility of detecting Majorana neutrinos at the Large Hadron-electron Collider, an electron-proton collision mode at CERN. We study the l+j+3jets (lj≡e,μ,τ) final states that are, due to leptonic number violation, a clear signature for intermediate Majorana neutrino contributions. Such signals are not possible if the heavy neutrinos have Dirac nature. The interactions between Majorana neutrinos and the Standard Model particles are obtained from an effective Lagrangian approach. We present our results for the total cross section as a function of the neutrino mass, the effective couplings, and the new physics scale. We also show the discovery region as a function of the Majorana neutrino mass and the effective couplings. Our results show that the Large Hadron-electron Collider may be able to discover Majorana neutrinos with masses lower than 700 and 1300 GeV for electron beams settings of Ee=50  GeV and Ee=150  GeV, respectively.